A comparative study of the Confucius Institute in the United Kingdom and the British Council in China. (April 2019) - Cai, Liexu
Since the first Confucius Institute was set up by the Chinese government for the promotion of Chinese language and culture overseas in 2004, the development of Confucius Institutes has become exponentially increasing. Currently, there are 29 Confucius Institutes in the United Kingdom among over 500 Confucius Institutes abroad; meanwhile, the activities of the British Council in China also became popular as one of the central paradigms for educational communication between China and the United Kingdom. Although there have been several studies on Confucius Institutes and British Council, respectively, little research exists about them from the international comparative perspective, with regard to both of them being cultural institutes abroad and the establishment of Confucius Institutes benefitting from the United Kingdom's experience in promoting its national languages and culture. This article aims to discover the general similarities and differences between Confucius Institutes and the British Council in three aspects: the organisation structures and culture diffusion models, the language teaching and learning resources and activities, and the cooperation that the two institutes have with the other organisations.